Digital Partnership: Combining Text Mining and GIS in a Spatial History of Sea Fishing in the United Kingdom, 1860 to 1900. Issue 1 (March 2015) - Schwartz, Robert M.
Abstract : The partnering of computer assisted qualitative data analysis (CAQDA) and GIS permits the analysis of voluminous historical documents and the incorporation of geographic perspectives to bring out spatial relationships that exist in the texts. The British Parliamentary investigations into sea fishing comprise a large body of evidence on the transformation of the trade, the exponential growth of the fish harvest, and the evolving recognition that over-fishing was underway. The use of CAQDA and GIS described in this article explores some 1, 800 pages of testimony given by fisherman, scientific experts, and regulatory officials before the Parliamentary commissions of enquiry in 1863–1866 and 1893–1894.